Fuzzy sliding mode variable structure control of a high-speed parallel PnP robot. (August 2021) - Wu, Guanglei; Zhang, Xuping; Zhu, Lina; Lin, Zirong; Liu, Jinguo
Highlights: A parallel PnP robot with efficient utilization of shop-floor space and high rotational capability. FSMVSC control variables are optimized for robot dynamics enhancement. Experimental results validate and show the effectiveness of control design. Tradeoff between acceptable computational cost and positioning accuracies. Abstract: This paper presents the analysis and experimental evaluation of robot dynamics and control for a four-limb parallel Schönflies-motion generator dedicating to fast pick-and-place operations, with a different topological architecture from its counterparts for efficient use of shop-floor space. The concise equation of motion is built with principle of virtual work to characterize the robot dynamics, which is integrated into the model-based control design. Fuzzy sliding mode variable structure control is adopted for the design of control scheme, aiming at buffeting suppression of the actuated joints and minimization of pose errors of robot end-effector. Numerical simulations are carried out along a trajectory of an industrial standard testing cycle to evaluate the performance, which is validated experientially by observing the joint dynamics. The results show the effectiveness of the developed dynamic control scheme for fast parallel pick-and-place robots.